Squamous cell carcinoma of the eviscerated bladder : A case report - Wachira Kochakarn (2018)
This is a report of a squamous cell carcinoma of the eviscerated bladder in a 52-year-old-Thai man. He had a history of pelvic fracture and failed urethroplasty. The bladder mucosa was eviscerated out from cystostomy tract after the spontaneous dislodging of the cystostomy tube. Squamous cell carcinoma developed at the eviscerated bladder 5 years later. The treatment consisted of radical cystectomy and ileal conduit with combination of radiotherapy. The patient died 7 months after operation due to liver metastasis. Correction or excision of the eviscerated bladder can prevent this kind of cancer.